PELATIHAN PEMANFAATAN POWER THRESHER DAN MANAJEMEN USAHA BAGI KELOMPOK USAHA PANEN PADI PEMULA DI SUBAK DESA KABUPATEN GIANYAR - I K. Satriawan; Yohanes Setiyo; I. A. Mahatma Tuningrat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2010)
Policy of product increase of national rice requires the development of adequate post harvest handling to improve efficiency, decreasing of losing crop, improving rendemen, added value, and competitiveness. This was done in order to improve earnings and prosperity of farmer in is the rural areas. Efforts to improve side of offfarm paddy especially its postharvest nowadays become attention to be handled seriously.Activity of this training aims at: (1) forming paddy crop group as development of business unit; ( 2) empowering of beginner paddy crop group so that they can apply postharvest technology and manage its agribusiness well; ( 3) training farmers to apply power thresher to minimize losing paddy crop. Participant target in this activity is group member of Subak Desa of Gianyar Regency.The result of this community services activity are as follows ( 1) Socialization of postharvest paddy have improved the understanding of beginner group member of paddy harvest so that they can contribute in lessening the lose paddy crop; ( 2) Forming crop group as the institution for empowering member of subak for developing of business unit; and ( 3) Applied training of power thresher can improve skillful harvest group members to minimize the lose of paddy crop in threshing.